Strategi Penataan Pedagang Ikan Segar Kaki Lima di Kota Kupang: Implikasi Terhadap Estetika dan Keberlanjutan Usaha - Fanggidae, Frits Oscar; Fanggidae, Apriana H. J.; Fanggidae, Jappy P. (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2024)
This study investigates the sustainability of street vendors (PKL) selling fresh fish in Kupang City, focusing on the perceptions of both consumers and vendors regarding urban aesthetic values. The findings reveal that, despite high consumer satisfaction with the services provided by the vendors, there is a preference for relocating their business activities due to the negative impact on urban aesthetics and safety. The vendors themselves acknowledge the importance of obtaining business permits and are generally open to relocation, provided that the new locations are strategic and equipped with adequate facilities. These results highlight the need for government intervention in organizing vendor locations and improving infrastructure to create a more aesthetic and sustainable business environment in Kupang City. This study offers valuable insights for the development of urban planning that supports business sustainability while enhancing urban aesthetics.